2016
DOI: 10.15376/biores.11.3.6968-6983
|View full text |Cite
|
Sign up to set email alerts
|

Physical and Mechanical Properties of Walnut Shell Flour-Filled Thermoplastic Starch Composites

Abstract: The goal of this work was to evaluate the technical feasibility of walnut shell flour (WSF) as substitute for wood in walnut shell flour/thermoplastic starch (WSF/TPS) composites. The effects of walnut shell flour (WSF), thermoplastic starch (TPS), and nanoclay on the physical and mechanical properties of WSF/TPS composites were investigated. The composite samples were formed in a Colin extruder with four-chamber heat with temperatures. Then, test samples were made using injection molding. The addition of up t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 38 publications
1
14
0
Order By: Relevance
“…Similar trend, i.e. enhanced mechanical properties with plant bers addition was observed for thermoplastic starch based system containing walnut [30] or banana leaf bers [35].…”
Section: Cms/cmc Composite Lms With Plant Llerssupporting
confidence: 77%
See 2 more Smart Citations
“…Similar trend, i.e. enhanced mechanical properties with plant bers addition was observed for thermoplastic starch based system containing walnut [30] or banana leaf bers [35].…”
Section: Cms/cmc Composite Lms With Plant Llerssupporting
confidence: 77%
“…In Figure 5 the moisture absorption of CMS/CMC lms and CMS/CMC/S composites containing 7 wt.% of various plant ller were presented. Water absorption depends on ller-matrix interphase as well as ller hydrophilic/hydrophobic character [30]. For polyole n-based composites it was reported that wood bers were primarily responsible for water absorption [31].…”
Section: Cms/cmc Composite Lms With Plant Llersmentioning
confidence: 99%
See 1 more Smart Citation
“…Native starch is a renewable natural resource, which can be extracted from different parts of the plants, such as seeds, fruits, leaves, tubers, and roots. It may come from a variety of vegetables and greens [56], including potato [34,46,[59][60][61][62][63][64], cassava [65][66][67][68][69][70][71], maize [28,38,[72][73][74][75][76], wheat [58], pea [5,45,[77][78][79][80], tapioca [2,81,82], corn [33,35,36,43,47,48,[83][84][85][86][87][88][89], pomegranate [90], sweet potato [53], and avocado [91]…”
Section: Thermoplastic Starchmentioning
confidence: 99%
“…In addition to these papers, the mechanical properties of Epoxy/WS composites were reported in some papers [21,22]. Sasari et al [23] evaluated the effect of WS on the tensile property of the Starch/WSP composite. Liu [24] investigated the effect of WS and KH550 on the properties of PLA/WS composite.…”
Section: Introductionmentioning
confidence: 99%